Cellular proliferation markers in peripheral and central fibromas: a comparative study - Garcia, Bruna Goncalves (2013)
Objective: To perform a comparative study of the cellular proliferation in the peripheral and central fibromas. Material and Methods: Immunohistochemistry for PCNA and the AgNOR technique were performed in 9 cases of peripheral odontogenic fibroma (POF), in 4 cases of odontogenic fibroma (OdF), in 8 cases of peripheral ossifying fibroma (PEOF) and 7 cases of ossifying fibroma (OsF). The Kruskal-Wallis and Mann-Whitney tests were used for the statistical analyses. Results: Mesenchymal component of the central lesions presented a higher mean number of AgNOR per nucleus and PCNA index than did the peripheral lesions (P≤0.05). The mean number of AgNOR per nucleus in the epithelial component proved to be higher in the OdF than in the POF (P≤0.05). The mesenchymal and epithelial components presented similar mean numbers of AgNOR per nucleus and PCNA index in the OdF, as well as a similar mean number of AgNOR per nucleus in the POF. Conclusions: The mesenchymal component may well play a role in the differences between the biological behaviour of the central lesions as compared to the peripheral lesions. Moreover, considering that the epithelial and mesenchymal components in odontogenic fibromas presented a similar proliferation index, more research is warranted to understand the true role of the epithelial components, which are believed to be inactive in nature, as well as in the development and biological behaviour of these lesions.